Long-Term Shifts in Faunal Composition of Freshwater Mollusks in Spring-Fed Rivers of Florida - Kusnerik, Kristopher M.; Means, Guy H.; Portell, Roger W.; Kannai, Alshina; Monroe, Mariah M.; Means, Ryan; Kowalewski, Michal (Frontiers in Ecology and Evolution, 2022)
Florida’s freshwater spring and river ecosystems have been deteriorating due to direct and indirect human impacts. However, while the conservation and restoration strategies employed to mitigate these effects often rely on faunal surveys that go back several decades, the local ecosystem shifts tend to have much deeper roots that predate those faunal surveys by centuries or millennia. Conservation paleobiology, an approach which enhances our understanding of the past states of ecosystems, allows for comparison of modern faunal communities with those prior to significant human impacts. This study examines the historical record of freshwater mollusk assemblages from two spring-fed river systems, the Wakulla and Silver/Ocklawaha Rivers. Specifically, we compared fossil assemblages (latest Pleistocene - early Holocene) and live mollusk assemblages in the two targeted river systems. Bulk sampling of the fossil record (20 sites: 70 samples: 16,314 specimens) documented relatively diverse mollusk assemblages that consist of a suite of native freshwater species that is relatively similar across the studied systems. In contrast, sampling of live communities (24 sites: 138 samples: 7,572 specimens) revealed depauperate species assemblies characterized by the absence of multiple native freshwater species commonly found in fossil samples, the widespread presence of introduced species, and dominance of brackish-tolerant species at the lower Wakulla River sites. Unlike fossil mollusk assemblages, live mollusk assemblages differ notably between the two river systems due to differences in relative abundance of introduced species (Melanoides tuberculata and Corbicula fluminea) and the presence of brackish-tolerant mollusks in the coastally influenced Wakulla River. The diverse, exclusively freshwater mollusk associations comparable across multiple river systems documented in the fossil record provide a historical perspective on the past state of freshwater river ecosystems complementing important data provided by modern surveys. The conservation paleobiology approach used in this study reinforces the importance of considering the historical ecology of an ecosystem and the utility of the fossil record in providing a historical perspective on long-term faunal changes.